Réponses

2014-01-28T20:14:25+01:00
A= x/5 = 3
A= (x*5)/5 = 3*5
A= x = 15

B= x/5 = 4/3
B= (x*5)/ 5 = (4/3)*5
B= x=20/3

C= x/5 = 3(x+1)
C= x/5 = 3x+3
C= x - 3x = 3*5
C= -2x = 15 
C= -2x/2 = 15/2 
C= -x = 15/2
C= x = -15/2

D= 3/7 x = -8(5x-7)
D= 3/7 x = - 40x + 56 
D= 3/7 x + 40x = 56
D= 3/7 x + 280/7 x = 56
D= 283/7 x = 56 
D= 283*7/7 x = 56*7
D= 283x = 392 
D= 283x/283 = 392/283 
D= x = 392/283 

2014-01-28T20:19:39+01:00
Bonsoir
a) x/5 = 15/5
x= 15

b) 3x = 20
x =20/3

c) x/5 = 3x +3
x = 15x + 15
x -15x = 15
-14x = 15
x = - 15/14

d) 3x/7 = -40x + 56
3x = - 280x + 392
3x +280x = 392
283x = 392
x = 392/283